Hands-on Domain in Learning Mathematics: Impact on Students’ Assessment Practices in Ghana - Maanu, Vivian; Bonyah, Ebenezer; Clark, Lauren Jeneva (Mathematics Education Journal, 2024)
The study purposefully explored the effect of Hands-on activities on pre-service teachers’ assessment in mathematics. The research employed a quasi-experimental design and utilized intact classes. One Hundred and Twenty (120) Level Three Hundred Pre-service teachers offering bachelor's degree programs in Junior High Education where purposively sampled. The one-group Pre-test and Post-test design was used to collect data for this study where each participant was evaluated first under the control condition and then under the treatment condition. The intervention was implemented within three weeks using manipulatives to ensure the practicality of the lessons. The post-test was also administered immediately after the intervention to determine its effectiveness. Results show a statistically significant ( ). Hence the study concluded that the use of hands-on activities improves on students’ performance in mathematics. It was recommended that, the teaching and learning of mathematics at the pre-tertiary level should incorporate hands-on activity method since it improves learners’ assessment practices.